Representasi Kerinduan dalam Lagu Umm Kulthūm Qiṣṣat Ḥubb Karya Aḥmad Rāmī: Analisis Semiotik Charles Morris - Roisah Fathiyatur Rohmah (Al-Ma‘rifah, 2021)
The purpose of this research is to reveal the representation of a male character’s longing for his lover in the song Qiṣṣat Ḥubb, a song full of emotion. The song was sung by Umm Kulthum, a famous singer from Egypt who has a big influence in the Arab world. The song Qiṣṣat Ḥubb was composed by an Egyptian writer named Aḥamd Rāmī. In the song Qiṣṣat Ḥubb, some signs have a deeper meaning. The study of meaning in this study uses Charles Morris’s theory of semiotics, which is divided into three, namely syntactic meaning, semantic, and pragmatic meaning. This study used a descriptive-analytic method by describing the data on the object of research, then continued with the analysis. The results of this study indicate that the syntactic meaning in the song Qiṣṣat Ḥubb is the sadness of a man because he reminisces with his late lover. The semantic meaning of this song is the confusion of a man who is abandoned by his lover. Meanwhile, the pragmatic meaning is the longing of a man for his lover which causes suffering and almost drives him crazy.